Trial Watch: Oncolytic viro-immunotherapy of hematologic and solid tumors - Pol, Jonathan G; Lévesque, Sarah; Workenhe, Samuel T; Gujar, Shashi; Le Boeuf, Fabrice; Clements, Derek R; Fahrner, Jean-Eudes; Fend, Laetitia; Bell, John C; Mossman, Karen L; Fucikova, Jitka; Spisek, Radek; et al. (Oncoimmunology, 2018)
Oncolytic viruses selectively target and kill cancer cells in an immunogenic fashion, thus supporting the establishment of therapeutically relevant tumor-specific immune responses. In 2015, the US Food and Drug Administration (FDA) approved the oncolytic herpes simplex virus T-VEC for use in advanced melanoma patients. Since then, a plethora of trials has been initiated to assess the safety and efficacy of multiple oncolytic viruses in patients affected with various malignancies. Here, we summarize recent preclinical and clinical progress in the field of oncolytic virotherapy.
Keywords: T-VEC; HF10; Pexa-Vec; REOLYSIN; DNX-2401; MV-NIS; CAVATAK; Maraba MG1